2011
DOI: 10.1016/j.nimb.2011.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam characterization of advanced luminescent materials for application in radiation effects microscopy

Abstract: The ion photon emission microscope (IPEM) is a technique developed at Sandia National laboratories (SNL) to study radiation effects in integrated circuits with high energy, heavy ions, such as those produced by the 88" cyclotron at Lawrence Berkeley National Laboratory (LBNL). In this method, an ion-luminescent film is used to produce photons from the point of ion impact. The photons emitted due to an ion impact are imaged on a position-sensitive detector to determine the location of a single event effect (SEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Although well above the operating temperature of many applications, this temperature regime shows that no significant nanoscale-enhanced sintering is observed in these systems. The poor irradiation stability observed in this work is similar to that seen in crystalline tungstate nanoparticles irradiated with heavy ions [23,24]. This in stark contrast to other amorphous ceramic nanoparticles and core@shell nanoparticles that have been explored, which suggests that the amorphous phase may be extremely important for radiation stability [25,26].…”
Section: Irradiation Stabilitysupporting
confidence: 51%
“…Although well above the operating temperature of many applications, this temperature regime shows that no significant nanoscale-enhanced sintering is observed in these systems. The poor irradiation stability observed in this work is similar to that seen in crystalline tungstate nanoparticles irradiated with heavy ions [23,24]. This in stark contrast to other amorphous ceramic nanoparticles and core@shell nanoparticles that have been explored, which suggests that the amorphous phase may be extremely important for radiation stability [25,26].…”
Section: Irradiation Stabilitysupporting
confidence: 51%
“…The luminescence spectra and decay kinetics of an InGaN/GaN MQW structure were investigated using UV and soft x-ray excitations [11]. The used excitation wavelength 325, 339 and 375 nm were chosen to generate carriers in GaN layers (325 nm and 339 nm) or in the InGaN QWs, only (375 nm).…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23][24][25] Branson et al conducted a study on the luminescence of In-GaN/GaN using IBIL, PL and cathodeluminescence measurement methods, and found that luminescence intensity depends on the specific excitation method employed in each measure-ment technique. [18] In this study, IBIL spectra of GaN/Al 2 O 3 at various depths were acquired by adjusting the incident ion energy to adapt to different film thicknesses. Subsequently, we conducted an in-depth analysis of the evolution of luminescence observed in GaN/Al 2 O 3 during irradiation.…”
Section: Introductionmentioning
confidence: 99%